A Proposed Model for the Post-Disaster Recovery Process in Turkey - Enginöz, Evren Burak (My University, 2018)
Turkey is a country, which experience more than one disaster in a year, especially earthquakes. Undoubtedly, it is a great building experience of post-disaster settlements and refugee camps all over the country. Therefore, in order to respond or to solve problems quickly in such extraordinary situations, there are Regulations on Reconstruction of Buildings for Earthquake Zones, post disaster recovery policies and development strategies. However, these regulations, policies and strategies do not include a prospective planning ora build back better (BBB) notion. They are just only aimed to provide shelters and urban infrastructures for disaster areas in short term, which cause more serious problems than disasters can do. Especially, inadequate regulations or unsuccessful urban recovery policies affect the psychology of survivors, their social and cultural lives, their memories, daily life activities and habits. In our previous researches we also observed that, when local expectations, demands and socio-cultural attributes are not taken into account, governmental urban planning and recovery policies cause noticeable reactions from survivors. Such as; to leave or not to use the post-disaster houses (PDH), to make deformations on or additions to them or to reconstruct their new buildings. It should not be forgotten that the success of the efforts to recover the cities after a disaster depends not only on the quality of the physical environment, but also on the sustainability of socio-cultural environment and networks. Additionally at the end of each application; taking lessons from the mistakes and using feed backs, for preferring more accurate solutions, will increase the success on the future processes. Thus, a model for post-disaster recovery process, in which considers spatial preferences, social expectations, current lifestyle and evaluates the BBB, user participation and feed backs, is required. Therefore, the objective of this paper is to find out the answers of question "howto generate a model for a post-disaster recovery process that includes solutions for BBB" to avoid recurrent problems in the future. In this context, the data obtained from the case study in Afyon-Dinar permanent PDH settlements will be used. The case study was done with the method of face-to-face interviews and conducted among the selected samples with the survivors who live or lived in permanent PDH. Within the scope of this case study; we can analyze appreciations of survivors on urban imaginaries, BBB and recovery strategies by inquiring correlations, using chi-square test (p< 0.05).